Conceptual neighborhood graphs for topological spatial relations - Santos, Maribel Yasmina (2009)
This paper presents the conceptual neighborhood graphs with the transitions between the topological spatial relations that can exist between a circular spatially extended point and a line. The final objective of this work is the use of the transitions in the prediction of a mobile user position in a road network. The conceptual neighborhood graphs were identified using the snapshot model and the smooth-transition model. In the snapshot model, the identification of neighborhood relations is achieved looking at the topological distance existing between pairs of spatial relations. In the smooth-transition model, conceptual neighbors are identified analyzing the topological deformations that may change a topological spatial relation. The obtained graphs and the corresponding topological distances between spatial relations can be used as an alternative, or as a complement, to map-matching techniques usually used to predict the positions of mobile users.